COPING STRATEGIES PREDICTING QUALITY OF LIFE AMONG PEOPLE LIVING WITH HIV/AIDS - OSAMIKA, Bamidele Emmanuel (PEOPLE: International Journal of Social Sciences, 2019)
Sub-Saharan Africa still been prevailed with a pandemic health and development problem known to be HIV/AIDS with the prevalence well noted in Nigeria. Immediately after been diagnosed with HIV/AIDS patients begin to experience poor quality of life. Coping strategies is identified as an influencing factor predicting quality of life (QoL) of people living with HIV/AIDS (PLWHA). This study examines coping strategies predicting quality of life of PLWHA attending antiretroviral therapy at the Hematology and Pathology Clinic, State Specialist Hospital, Akure, Ondo State, Nigeria. Using multiple regression analysis, a cross sectional design and a purposive sampling method was employed to sample two hundred and ten PLWHA. A structured questionnaire focusing on socio-demographic profile, coping strategies and the World Health Organization Quality of Life Questionnaire for HIV-Brief Version (WHOQOL-BREF) instrument was administered to the participants. The results showed that coping strategy significantly predict physical (R=0.41;R2=0.17; p<.05), psychological (R=0.55;R2=0.28; p<.05), social relationship (R=0.50;R2=0.25; p<.05), environment (R=0.55;R2=0.31; P<.05), spirituality (R=0.51;R2=0.26; p<.05) domains and overall WHOQOL-BREF (R=0.58;R2=0.21; p<.05) of PLWHA. However, coping strategy didn’t significantly predict level of independence domain (R=0.25;R2=0.06; p>.05) of quality of life. Specifically, self–distraction (B=0.11;β=0.21; p<.05), active (B=-0.14;β=-0.21; p<.05), acceptance (B=0.12;β=0.19; p<.05) and religion (B=0.08;β=0.15; p<.05) coping strategies independently predict overall WHOQOL-BREF of PLWHA. Also, highest and lowest mean score was recorded in environment and spirituality domains of WHOQOL-BREF respectively. Among PLWHA, coping strategy is essential indicator for the improvement of QoL. Coping strategy plays an important role in the determinant of domains and overall quality of life of PLWHA.